Sociodemographic Characteristics of Females Married less than 18 Years - Alaa Hussain, Nibras; Hameed Mohammed, Saif; Amerabd al Hussain, Laith (International Journal of Psychosocial Rehabilitation, 2020)
Background: Many young males and females do not have a chance to work out their right to select and choose their partner during marriage. Child marriage can be defined as marriage occurring at an age below 18 years old, before she becomes (physiologically, physically, and psychologically) appropriate for holding the duties of marriage and childbearing. In the Arabic community, early married females represented protection for them, and battles and community difficulties are considered one of the very important causes of early marriage. So the aim of the study is to display some sociodemographic characteristics of females married before 18 years of age and find the most common causes behind this marriage. Results: Most of the females were 15 years or less, unemployed, knew their husband before marriage, had pregnancy complications, and were happy with their husband. There were significant associations between early marriage at 15 years and less and incomplete education and the occurrence of pregnancy complications. Conclusion: This study found that social and personal causes are mainly responsible for early marriage.